2021
DOI: 10.1111/psyg.12741
|View full text |Cite
|
Sign up to set email alerts
|

Elderly people's quality of life in rural areas of Turkey and its relationship with loneliness and sociodemographic characteristics

Abstract: Background:The aim of the present study was to examine the relationships between loneliness, quality of life and the factors that may be related to the quality of life in individuals ≥65 years old living in rural areas of Turkey. Methods: The World Health Organization Quality of Life Instrument Older Adults Module (WHOQOL OLD) and Loneliness Scale for the Elderly (LSE) was administered to 427 elderly participants. Multiple linear regression was used to determine the variables that affected QOL. Results: The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
(55 reference statements)
0
4
0
5
Order By: Relevance
“…Bu çalışmada kadınların erkeklerden, evli olmayanların evlilerden ve üniversite mezunu olanların diğer eğitim düzeyindeki yaşlılara göre yalnızlık düzeyinin düşük olduğu bulunmuştur. Çalışmamızla tutarlı olarak bazı çalışmalarda yaşlı erkeklerde kadınlara göre yalnızlık düzeyinin daha fazla [29,30], bazı çalışmalarda kadınlarda erkeklerden [31,32], bazı çalışmalarda ise cinsiyete göre herhangi bir farklılık olmadığı belirtilmektedir [33][34][35]. Yalnızlık durumu bireylere göre değişiklik gösterse de kadınların; iletişim kurma, sosyalleşme rollerini erkeklere göre daha kısa sürede ortaya koymalarının kadınların yalnızlık puanını etkilediği düşünülebilir.…”
Section: Tartışma Ve Sonuçunclassified
“…Bu çalışmada kadınların erkeklerden, evli olmayanların evlilerden ve üniversite mezunu olanların diğer eğitim düzeyindeki yaşlılara göre yalnızlık düzeyinin düşük olduğu bulunmuştur. Çalışmamızla tutarlı olarak bazı çalışmalarda yaşlı erkeklerde kadınlara göre yalnızlık düzeyinin daha fazla [29,30], bazı çalışmalarda kadınlarda erkeklerden [31,32], bazı çalışmalarda ise cinsiyete göre herhangi bir farklılık olmadığı belirtilmektedir [33][34][35]. Yalnızlık durumu bireylere göre değişiklik gösterse de kadınların; iletişim kurma, sosyalleşme rollerini erkeklere göre daha kısa sürede ortaya koymalarının kadınların yalnızlık puanını etkilediği düşünülebilir.…”
Section: Tartışma Ve Sonuçunclassified
“…Hasil analisis 10 jurnal terdapat 7 artikel yang menyebutkan bahwa tingkat Pendidikan terbukti dapat meningkat QOL (Quality Of life) pada lansia (Indrayani, 2018;Ridwan, 2021;Arif & Yanuar, 2016;Çam et al, 2021;Hajian et al, 2017;Faronbi et al, 2020;Elsous et al, 2019). Tingkat Pendidikan yang mempengaruhi kualitas hidup lansia terjadi pada lansia yang mempunyai Pendidikan tinggi di bandingkan pada lansia yang memiliki Pendidikan rendah atau pun tidak bersekolah (Wahid et al, 2021).…”
Section: Pembahasanunclassified
“…Berdasarkan analisis 10 artikel ada 4 artikel yang menjelaskan bahwa pendapatan merupakan salah satu faktor predictor untuk meningkatkan skor kualitas hidup pada Lansia (Martalena, 2020;Ardiani et al, 2019;Gobbens & van der Ploeg, 2021;Çam et al, 2021). Pendapatan rendah dapat mempengaruhi kualitas hidup lansia hal ini Dikarenakan penghasilan rendah dapat mengganggu pengobatan lansia, khususnya terkait diet dan penggunaan obat-obatan, jika hal ini tidak tercakup oleh sistem perawatan maka kesejahteraan lansia menjadi terganggu (Nugrahadi Dwipasca Budiono, 2021).…”
Section: Pembahasanunclassified
See 1 more Smart Citation
“…Addressing social isolation among older people is crucial for both health professionals and policymakers (Robins et al, 2018). However, those older people who engage in social activities have found their lives to be more satisfactory as the interaction with others has had a positive effect on their cognitive and physical condition, contributing to their life satisfaction and subjective well-being (Bae & Kim, 2021;Çam et al, 2021;Hwang et al, 2018;Oh et al, 2021;Popovic & Masanovic, 2019). Fu et al (2018) reported a positive correlation between participation in social activities and psychological well-being in nursing home residents in China.…”
Section: Introductionmentioning
confidence: 99%